The Occurrence of FUS Mutations in Pediatric Amyotrophic Lateral Sclerosis: A Case Report and Review of the Literature. (July 2020) - Picher-Martel, Vincent; Brunet, Francis; Dupré, Nicolas; Chrestian, Nicolas
Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease affecting both upper and lower motor neurons and leading to progressive paralysis. Most cases are sporadic, and the symptoms generally begin in the sixth or seventh decade. Juvenile ALS appears in a rare subgroup of patients with onset before the age of 25 years old. Contrary to the classical adult phenotype where 90% of cases are sporadic, most cases of juvenile ALS are caused by a genetic mutation in either SOD1 (superoxide dismutase one), SETX (senataxin), or FUS (fused in sarcoma). In the pediatric population, ALS is more infrequent and rarely considered in the differential diagnosis. There are few reports of ALS in children. Here, we describe a 14-year-old boy with a very fast progressing classical ALS phenotype and tremor caused by a c.1554_1557delACAG mutation in FUS . Our review of the literature advocates that pediatric ALS is highly suggestive of FUS mutations and that gene should be tested in children presenting with symptoms of ALS. The children with FUS -related ALS may have no family history and present initially with learning disabilities, tremor, and mild motor developmental delay.